2018
DOI: 10.1039/c8ob00608c
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the biosynthesis of the antifungal strobilurins

Abstract: Prestrobilurin A, formed via benzoate and cinnamate, has been identified as the first enzyme free intermediate in strobilurin biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The proposed rearrangement mechanism involves the unusual migration of a carboxylate as proven by the isotopic labelling studies 10 . Similar processes are known, for example, during the mechanism of methylmalonate mutase and during the biosynthesis of the tropane alkaloid hyoscyamine from littorine 28 (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The proposed rearrangement mechanism involves the unusual migration of a carboxylate as proven by the isotopic labelling studies 10 . Similar processes are known, for example, during the mechanism of methylmalonate mutase and during the biosynthesis of the tropane alkaloid hyoscyamine from littorine 28 (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Isotopic feeding experiments have shown that strobilurin A 1 10 and oudemansin A 2 11 are polyketides, unusually derived from a benzoate starter unit derived by the degradation of phenylalanine via cinnamate. In fungi, polyketides are produced by iterative polyketide synthase (PKS) enzymes that extend acyl coenzyme A (CoA) starter units using decarboxylative Claisen-type reactions with malonyl CoA 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The choice of reductant proved to be critical with regard to the final geometry of the double bond. For instance, triethylsilane and methyl formate gave E / Z ratios of 2:1 and 2.5:1, respectively. More promising results for the generation of the desired ( E )‐isomer were obtained using triethylammonium formate .…”
Section: Resultsmentioning
confidence: 99%
“…6 Isotopic feeding experiments showed that strobilurin A 1 is a polyketide. 8 The biosynthetic steps to strobilurin A 1 have been reported recently by our group (Scheme 1). 6 Genome sequencing of S. tenacellus and S. lutea revealed that each organism harboured a biosynthetic gene cluster (BGC) responsible for the production of 1.…”
Section: Introductionmentioning
confidence: 95%